Analysis of photodegradation and reaction kinetics of textile organic dyes on caesalpinia sappan, lawsonia inermis and areca catheu using spectroscopic methods for solar cell application - Siti Rokhmanila, Sukardi; Ahmad Nazri, Dagang; Hasiah, Mat Salleh; Wan Hafiza, Wan Hassan; Nik Aziz, Nik Ali; Muhamad Zahim, Sujod (Semarak Ilmu Publishing, 2025)
Organic dyes are part of the textile industrythat have a negative impact on the environment. Photodegradation using sunlight can reduce the environmental impact as it has the potential to convert complex organic dyes into simpler and less harmful compounds. Natural dye-based hybrid solar cells have the lowest cost among solar cell technologies, givesthe lowest photochemical conversion efficiency. The problematic factor in Dye-Sensitised Solar Cells (DSSC)is the use of electrolyte type, either gel or solution, which lead to theleakage, dyeinstability,and evaporation.The aim was to analyse the photodegradation reaction kinetics of organic dyes in Caessalpinia Sappan, Medina Lawsonia Inermis, YemeniLawsonia InermisandAreca Catheuusing spectroscopic methods. This research focuses on the potential of natural dyes extracted from these sources as sensitizers in DSSC. The stability of natural dye was analysed using the photodegradation reaction kinetics oforganic dyes before and after treatment using advanced spectroscopic methods. The extracted natural dyes were determined their optical absorption and functional group through Ultra Violet-Visible(UV-Vis)spectrophotometer, UV-Vis and Fourier Transform Infrared Spectroscopy (FTIR), respectively.The photo degradation proses of natural dyes were done under radiation of sunlight for four weeks with measured their photodegradation efficiency at every weeks.After plasma treatment using APPJ, a positive effect on the stability and colour of anthocyanins was observed.The results showed an increase in the percentage of photodegradation after APPJ treatment on Medina Lawsonia Inermisand Yemeni Lawsonia Inermis. While Caessalpinia Sappan, and Areca Catheushowed a slight changecompared to before plasmatreatment. The FTIR spectra of the natural dyes showed the presence of functionalised hydroxyl compounds and C-O groups. After plasmatreatment, stronger functional group peaks were observed and new chemical bonds were formed.